Biblical perspectives : early use and interpretation of the Bible in light of the Dead Sea scrolls : proceedings of the First International Symposium of the Orion Center for the Study of the Dead Sea Scrolls and Associated Literature, 12-14 May 1996 - Stone, Michael E., 1938-; Chazon, Esther G. (Studies on the Texts of the Desert of Judah, 1998)
This volume explores the use and interpretation of the Bible in the Dead Sea Scrolls and associated apocryphal, early Christian and rabbinic literature. Interpretive interests, techniques and traditions are examined in many types of ancient works: rewritten bibles, pseudepigrapha, legal codes, prayers, sapiential texts, admonitions and historical treatises. The authors highlight the contribution of the new finds from the Judean Desert to such major issues as attitudes to the Bible and the Law in antiquity, continuity and innovation vis a vis the biblical world, common and unique dimensions of interpretation among different groups in the Second Temple and Rabbinic periods in particular, the Qumran sectarians and their opponents, New Testament authors and rabbinic Sages.